ANALISIS KINERJA TIANG DENGAN VARIASI KEMIRINGAN DI DERMAGA “SJ” BANDAR LAMPUNG - Dede Oktaferdian; Sunarjo Leman (JMTS: Jurnal Mitra Teknik Sipil, 2021)
The design of the jetty cannot be separated from the use of piles as a foundation that supports the upper structure. The pile configuration affects the strength and stability of the structure. It may consist of only vertical piles or a combination of vertical and batter piles. This study analyzes and compares 10 types of pile configurations intending to determine the best pile configuration among the types analyzed. Type 1 is a pile configuration that is in accordance with the field planning of “SJ” jetty which consists of only vertical piles and type 2 to type 10 is a pile configuration that consists of a combination of vertical and batter piles with a slope ranging from 1H:12V to 1H:4V. The best configuration is determined based on the strength (capacity ratio), stiffness (deflection that occurs), and the axial bearing capacity of the pile. The process of modeling and analyzing the pile configurations are done using Midas Gen. The results showed that pile configuration type 8 with a combination of vertical and batter piles with a slope of 1H:6V is the best configuration with the smallest deflection and the axial forces of the vertical and batter piles are almost equal.ABSTRAKDesain dermaga tidak dapat dipisahkan dari penggunaan tiang sebagai fondasi yang menyangga struktur bagian atas. Konfigurasi tiang berpengaruh pada kekuatan dan stabilitas dari struktur dermaga. Konfigurasi tiang dapat terdiri dari tegak seluruhnya maupun kombinasi antara tiang tegak dan miring. Penelitian ini menganalisis dan membandingkan 10 tipe konfigurasi tiang dengan tujuan mendapatkan konfigurasi tiang terbaik di antara tipe-tipe yang dianalisis. Tipe 1 adalah konfigurasi tiang yang sesuai dengan perencanaan dermaga “SJ” berupa tiang tegak seluruhnya dan tipe 2 hingga tipe 10 adalah konfigurasi kombinasi tiang tegak dan miring dengan kemiringan 1H:12V hingga 1H:4V. Konfigurasi tiang terbaik ditentukan berdasarkan kekuatan (capacity ratio), kekakuan (defleksi yang terjadi), dan daya dukung aksial tiang. Model dan proses analisis dari seluruh konfigurasi tiang menggunakan program Midas Gen. Hasil analisis menunjukkan bahwa konfigurasi tiang tipe 8 dengan kombinasi tiang tegak dan miring dengan kemiringan 1H:6V adalah konfigurasi terbaik dengan defleksi terkecil serta gaya aksial tiang tegak dan miring yang hampir sama.